Fateful Beauty : Aesthetic Environments, Juvenile Development, and Literature, 1860-1960. - Mao, Douglas (Princeton University Press, 2010)
When Oscar Wilde said he had "seen wallpaper which must lead a boy brought up under its influence to a life of crime," his joke played on an idea that has often been taken quite seriously--both in Wilde's day and in our own. In Fateful Beauty, Douglas Mao recovers the lost intellectual, social, and literary history of the belief that the beauty--or ugliness--of the environment in which one is raised influences or even determines one's fate. Weaving together readings in literature, psychology, biology, philosophy, education, child-rearing advice, and interior design, he shows how this idea abet.